INSTAGRAM SEBAGAI MEDIA SOSIAL DALAM MEMBENTUK PERSONAL BRANDING NASYA MARCELLA - Dina Sudarmika; Novia Sella (Commed : Jurnal Komunikasi dan Media, 2022)
Currently, technology is evolving very rapidly. One of the things people can do on in this digital era is to build strong personal branding through social media. Personal branding it based on the values of life and has a high relevance to who one is. This research uses CMC concept (Computer Mediated Communication). This research uses a type of qualitative research with descriptive methods such as conduct direct research, conduct in-depth observations and describe facts in the field. In the research, researchers explored Nasya Marcella's personal branding through Instagram social media. Nasya Marcella is an actress who has values, qualities, principles and has had a positive image in the public. so that it became the hallmark of the figure of Nasya Marcella. Nasya Marcella communicates all of her works through uploading photos or videos on social media Instagram so that it creates a public perception of her. In this research, Nasya Marcella has fulfilled all the main elements of the personal branding formation process according by Peter Montoya.